A mechanics comparison between landing from a countermovement jump and landing from stepping off a box - Afifi, M.; Hinrichs, R. N. (Journal of Applied Biomechanics, 2012)
It is common practice to study jump landing mechanics by having subjects step off a box set at a certain height instead of landing from a jump. This practice assumes that the landing mechanics are similar between stepping off a box and a countermovement jump as long as the heights can be matched. The mechanics of the two methods had never been compared when landing from identical heights. Thus, the purpose of this study was to compare the mechanics of landing from a countermovement jump to landing from a step-off. Participants performed three maximal countermovement jumps. The mechanics of one countermovement jump was compared with a center of mass fall height matched step-off landing. The step-off landing showed a more rapid time to peak ground reaction force (GRF) in both genders and greater GRF peak and loading rate in males only. No difference was observed between joint angles at initial contact; however, the countermovement jump showed significantly greater joint flexion angles at peak GRF for both genders. EMG showed greater muscle activity during the countermovement jump condition in all subjects. It was concluded that countermovement jump landings are different from step-off landings; thus, results from analyses involving step-off landings should be taken with caution if the aim is to relate them to landing from a jump.